"Novos" territórios eólicos e os impactos socioambientais no município de Marcolândia, Estado do Piauí - Campêlo, Jaerle Rodrigues (2018)
The energetic issue is getting a high relevant in the global discussion in relation to beget electric energy, specially because the historic process of electric production has a lot of problem in the way to generation and obtainment, becoming a question worldwide, because the needs of continuously increase of global demand, having as a reason the growing of population and the economy in the globalization society. The energetic future with the persistence of the fossil fuel shows a bunch of the problem for the global society, such as: environmental inequality, air pollution, global warming, among others. In Brazil, the wind energy has huge space to grow, but still need of investment to take off; this sector of economy is one of the most promising and environmentally sustainable sources. The countryside is increasingly being replaced by non-agricultural activities, which has caused significant changes in its landscape, for example, due to the installation of large wind farms, but the impacts on the generation and use of this energy source are both positive and negative. The municipality of Marcolândia, located in the Brazilian Northeast, stands out in this new environment of clean energy, due to the significant amount of wind farms installed in the "new" wind farms. To do so, the present research sought to investigate the impacts of the implementation of a wind farm, taking as an example the municipality of Marcolândia-PI, inserted in the Chapada do Piauí Wind Complex, discussing local transformations, mainly in the physical environment (landscape) and Social. This work is descriptive, with a bibliographical survey and carried out by means of a case study. The research revealed that the most significant impacts on the physical environment are related to fauna collision, mainly animals that fly with wind turbine propellers, causing the mortality of bats. The socio-environmental impact has a direct relationship with the leasing of land for the implementation of wind farms, the increase of the purchasing power of the population, as well as the generation of jobs for the local labor only in the initial phase of the enterprise, due to its low qualification.